Remembering our intimacies : moʻolelo, aloha ʻāina, and ea - Osorio, Jamaica Heolimeleikalani (Indigenous Americas., 2021)
"Recovering Kānaka Maoli (Native Hawaiian) relationality and belonging in the land, memory, and body of Native Hawai'i"--